Implementation of blue economy in Bangsring underwater for enhancing the quality of environmental, economic, and social aspects of the community - Siswanto, Adil (YAYASAN MITRA PERSADA NUSANTARA, 2025)
This study aims to explore the implementation of the blue economy concept and its impact on the environment, economy, and social conditions of the community surrounding a tourist destination. The research employs a qualitative approach, utilizing observation, interviews, and documentation techniques to gather relevant data. These methods provide a comprehensive understanding of how the blue economy principles are applied in the context of sustainable tourism. The data collected was analysed using the Miles and Huberman method, which involves data reduction, data display, and conclusion drawing. This analytical approach allows for an in-depth examination of the alignment between the blue economy principles and their practical application. The findings indicate that while the implementation of the blue economy concept largely aligns with its core principles, there are still areas that require further attention for continued development. Specifically, the research highlights the need for enhanced efforts in certain aspects of sustainability and community involvement. Despite these areas for improvement, the overall impact of the blue economy implementation has been positive, contributing to improved environmental conditions, economic growth, and the social welfare of the surrounding community. These results suggest that the blue economy holds significant potential for fostering sustainable development in tourism, benefiting both the environment and local populations.